Outcomes of Children With Chronic Intestinal Failure: Experience Over 2 Decades at a Tertiary Paediatric Hospital. Issue 3 (September 2019) - Jo, Sz-Ying C.; McCallum, Zoe; Shalley, Helen; Peterkin, Megan; Rogers, Elizabeth; Paxton, Georgia; Wong, Theodoric; Bines, Julie E.
ABSTRACT: Background and Aims: The aim of the study was to aid decisions on prognosis and transplantation; this study describes the outcome of children with intestinal failure managed by the multidisciplinary intestinal rehabilitation program at the Royal Children's Hospital, Melbourne. Methods: Retrospective review of children requiring parenteral nutrition (PN) for >3 months who were assessed for home PN between 1991 and 2011. Results: A total of 51 children were included. Forty-two (82%) had short bowel syndrome (SBS), 5 (10%) had chronic intestinal pseudo-obstruction syndrome, and 4 (8%) had congenital enteropathies. Median small bowel length for patients with SBS was 45 cm (interquartile range 30–80) or 23.9% of the expected length for age (interquartile range 17.0%–40.6%). Overall survival rate was 84% (43/51). Mortality in children (n = 7) occurred after a median of 13.2 months (range 6.2–29.2) with intestinal failure–associated liver disease (IFALD) being the only predictor ( P  = 0.001). Out of 50 children 21 (42%) had IFALD. Children who were premature ( P  = 0.013), had SBS ( P  = 0.038), and/or frequent sepsis ( P  = 0.014) were more likely to develop IFALD. PN weaning occurred in 27 of 35 (77%) SBS survivors, after a median of 10.8 months (up to 8.2 years), with longer residual small bowel ( P  = 0.025), preservation of the ileocecal valve ( P  = 0.013) and colon ( P  = 0.011) being predictors. None of 5 (0%) patients with chronic intestinal pseudo-obstruction syndrome and 2 of 4 (50%) patients with congenital enteropathies weaned off PN. Overall sepsis rate was 7.3 episodes/1000 line days. Frequency of sepsis and longevity of central lines improved with time as patients grew older (both P  < 0.001). Conclusions: Long-term PN with intestinal rehabilitation was effective in treating most children with intestinal failure. Children with severe refractory IFALD may have benefited from intestinal transplantation. Abstract : Supplemental Digital Content is available in the text